Trade in Agricultural Products between Serbia and Russia in the Light of Preferences and Sanctions between Russia and Western Countries - Baturan, Luka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
In the following paper, we analyze the current customs law that regulates trade in agricultural products of Serbia and Russia, in the light of on-going economic sanctions between Russia to Western countries. Methods used to interpret legal norms are mostly economic ones. The goal is to show allocative (kao što vidiš spellcheck ne poznaje ovu reč, bolje “allocation”) and welfare effects in the current institutional frame formed by the sanctions, so that could serve as a scientific base for adequate state policy. High agricultural incentives in developed countries makes Serbian producers and farmers unable to compete on the world market. On the other side, regulations on customs between Serbia and Russia favors Serbian producers on the Russian market. Agricultural production and export from Serbia will increase thanks to Russian sanctions to Western countries. However, if the Serbian producers fail to organize competitive production, after the sanctions expire, they will lose gained positions on Russian market. Key words: Free trade agreement, sanctions, Russia, European Union, export